Isolated splenic high-grade serous carcinoma: A case report - Ralph Rogers; Sarah Ehmann; William P. Tew; Vance Broach (Elsevier, 2021)
We present a unique case of high-grade serous carcinoma isolated to the spleen at the time of diagnosis, without any tumor present in the ovary, fallopian tubes, omentum or uterus, which was pathologically consistent with metastatic Mullerian carcinoma. Tumor sequencing with the MSK-IMPACT (Memorial Sloan Kettering-Integrated Mutation Profiling of Actionable Cancer Targets) multigene tumor panel test was performed, which revealed somatic mutations in PALB2 and in ARID1, as well as a TP53 hotspot mutation.